Benefits of rural-urban interactions for sustainable food security in Iran (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
Cities and rural areas, as two human settlements, have long interacted with each other, and these interactions have many benefits for producing better products and food security. However, despite the importance of benefits in rural-urban interaction, identifying, improving, and investing them in rural areas of Iran has always been neglected. Therefore, in addition to identifying the benefits of interactions, this study investigates the causal relationship between them and sustainable food security in villages in the southeast Tehran province in Iran. Four hundred questionnaires were completed among farmers by simple random sampling. The findings, conducted in a descriptive-analytical and questionnaire based manner, show the positive effect of rural-urban interactions on sustainable food security. The product transport variable has the most significant impact, and agricultural services and production support have a negligible effect on sustainable food security. Villagers' access to roads (proximity to farms), suitable ways to deliver agricultural and non-agricultural products to the city, warehousing, refrigeration, and packaging services, widening roads between farms, and market access are the key factors influencing food security.